Governing school nutrition: principal leadership and policy implementation in indonesia's free meal program - Hamid Hamid; Nurul Astuty Yensy (Jurnal EDUCATIO: Jurnal Pendidikan Indonesia, 2026)
This study examines the governance dynamics of Indonesia's Free Nutritious Meal Program (MBG), a strategic policy aimed at improving student welfare, health, and learning readiness through school-based nutrition services. Focusing on the interplay between principal leadership and policy implementation, a qualitative case study was conducted at a public senior high school in Mukomuko Regency. Data were collected through semi-structured interviews, observations, and document analysis involving a principal, two vice principals, four teachers, two education staff, and four students, following the Miles and Huberman interactive model for analysis. The results reveal three main insights: MBG program governance involves five interconnected activities—planning, coordination, coordination, implementation, supervision, evaluation, and reporting; principal leadership plays a pivotal role in orchestrating these activities; and persistent challenges include coordination with external stakeholders, resource allocation, and monitoring consistency. The study concludes that effective principal leadership is central to successful MBG implementation, yet governance gaps remain. The novelty lies in empirically examining the underexplored leadership-governance nexus within Indonesia's MBG policy implementation at the secondary school level. Practically, the findings suggest that strengthening principal training in policy coordination and stakeholder management is essential. This study contributes to educational governance literature by demonstrating that policy success in school-based nutrition programs depends not only on resource provision but also on nuanced leadership strategies that navigate complex local governance arrangements.